Unfermented grape juice reduce genomic damage on patients undergoing hemodialysis. (June 2016) - Corredor, Zuray; Rodríguez-Ribera, Lara; Coll, Elisabeth; Montañés, Rosario; Diaz, Juan Manuel; Ballarin, José; Marcos, Ricard; Pastor, Susana
Abstract: Chronic kidney disease (CKD) patients in dialysis (HD) are considered to be submitted to a continuous oxidative stress. This stress can cause damage on DNA and, consequently, contribute to the high levels of DNA damage observed in these patients. Due to the well-known role of polyphenols as antioxidant agents we proposed its use to reduce the levels of genotoxicity present in HD-CKD patients. The objective of this study was to evaluate the antigenotoxic effects of unfermented grape juice (UGJ) on HD-CKD patients. The levels of DNA damage were analyzed using different biomarkers, such as breaks and oxidized DNA bases by the comet assay, chromosome damage by the micronucleus test. In addition, TEAC (Trolox equivalent antioxidant capacity) was also evaluated. Thirty-nine patients were followed for six months, of whom 25 were supplemented by UGJ and 14 were not supplemented. The obtained results showed a significant decrease in the underlying levels of oxidative DNA damage, in the supplemented group. Regarding the clinical parameters, LDL and cholesterol, were significantly reduced in the patients studied after the supplementation period, although cholesterol was also decreased in the non-supplemented patients. In conclusion, in our studied group the supplementation with UGJ reduced the levels of oxidative DNA damage of HD-CKD patients. Graphical abstract: The unfermented grape juice supplement decreases the levels of genomic damage in hemodialysis patients. Highlights: Grape juice supplementation reduces DNA damage levels in HD-CKD patients. UGJ supplementation did not modify the levels of chromosomal damage. Evaluated biochemical parameter did not change with supplementation.